The theatre and its double - Artaud, Antonin, 1896-1948 (Theatre makers /, 2024)
"This new translation of Artaud's canonical text from 1938 retains the idiosyncratic nature of some of the author's writing while communicating the fervour and ambition that it contained. Translated into a contemporary English that accurately conveys the detail and impact of the original, this is the first English-language version of The Theatre and its Double to be at once faithful to the original and more easy for today's readers to understand. It brings together all of the key texts that formed the 1938 Le thť́re et son double, including 2 texts not included in Victor Corti's established translation - 'Le thť́re et la culture' and 'Le thť́re alchimique' - as well as a translation of 'Le thť́re de Sřaphin', which was intended for, but omitted from, the original 1938 publication. By including, too, a newly translated selection of Artaud's letters about the book's original publication and the author's concept of a 'theatre of cruelty', we are able to form a fuller appreciation of Artaud's objectives. The commentary further contextualizes this material within Artaud's broader oeuvre, from his collaboration with the Surrealist group through to his plans to stage his own adaptation Les Cenci in 1935. The contributions of key works of Artaud scholarship from the last two decades are summarised and contextualised, including work in the area by Adrian Morfee, Kimberly Jannarone and Stephen Barber. Additionally, a selection of Artaud's correspondence with his publisher and friends on the subject of 'cruelty' and on his ambitions for his book has been newly translated here to complement the correspondence that already exists as part of the volume. These include letters to Roger Blin, Jean-Louis Barrault, Anas̐ Nin, Andr ̌Rolland and Jean Paulhan. Each chapter features endnotes clarifying Artaud's numerous, often obscure allusions and references to help today's student. Ultimately, we come to understand how these writings manifest and mobilise a particular Artaudian concern for art and life to operate inseparably, and Artaud's articulation of his own ambition, placing these in the context of his practice and European mid-century practice more widely. A welcome addition any theatre-lover's or student's bookshelf, this is a much-needed opportunity to gain clear and faithful insights into Artaud's theatre"--